2009
DOI: 10.3177/jnsv.55.400
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fatty Acid Composition, Estimated Desaturase Activities, and Intakes of Energy and Nutrient in Japanese Men with Abdominal Obesity or Metabolic Syndrome

Abstract: SummaryTo examine predictive factors for abdominal obesity or metabolic syndrome, we investigated the association of plasma fatty acid composition, estimated desaturase activity, and nutrient intakes, with abdominal obesity or metabolic syndrome in Japanese males. Clinical characteristics, the fatty acid composition of plasma cholesteryl esters, and energy and nutrient intakes were analyzed in 3 groups: metabolic syndrome (MS, n ϭ 24), abdominal obesity (OB, n ϭ 43), and control ( n ϭ 27). The estimated desatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…The spot corresponding to PL was scraped from the plate and transmethylated with 2 ml acetyl chloride: methanol (5:50; v/v) at 90˚C for 2 h. Heptadecanoic acid (17:0) served as an internal standard. FA methyl esters were analyzed by gas-liquid chromatography (GC-2014; Shimadzu Corp., Kyoto, Japan) with a 25 m x 0.5 mm capillary column (HR-SS-10; Shinwa Chemical Industries Ltd., Kyoto, Japan) as previously described (28). Statistical analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…The spot corresponding to PL was scraped from the plate and transmethylated with 2 ml acetyl chloride: methanol (5:50; v/v) at 90˚C for 2 h. Heptadecanoic acid (17:0) served as an internal standard. FA methyl esters were analyzed by gas-liquid chromatography (GC-2014; Shimadzu Corp., Kyoto, Japan) with a 25 m x 0.5 mm capillary column (HR-SS-10; Shinwa Chemical Industries Ltd., Kyoto, Japan) as previously described (28). Statistical analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…The plasma phospholipid fraction was used to obtain the desaturase indices in our study because the turnover of plasma phospholipids is slower than that of plasma triglyceride fatty acids and there is minimal day-to-day variation; however, it is controversial which fraction of desaturase indices is most appropriate to [37][38][39][40] . In conclusion, DHA content in plasma phospholipids had a negative association with SCD indices, which may explain the anti-obesity effect of DHA.…”
Section: Discussionmentioning
confidence: 99%
“…In 301 Swedish men (60 years of age), for example, FADS1 products (20:4, 6/20:3, 6) in adipose tissue and plasma phospholipids were inversely correlated with obesity and insulin resistance, whereas FADS2 products (18:3, 6/18:2, 6) showed a positive association ( 74 ). A study involving 97 Japanese men ( ‫ف‬ 50 years of age) showed reduced 20:4, 6/20:3, 6 (FADS1 product), but higher levels of 18:3, 6/18:2, 6 (FADS2 product) in obese and MetS patients versus control ( 75 ). Feeding C57BL/6J mice a high-fat diet (60% energy as fat) induces obesity, insulin resistance, and hepatosteatosis (fatty liver) and suppresses the plasma and hepatic 20:4, 6 to 18:2, 6 ratio by ‫ف‬ 60% compared with lean euglycemic mice fed a low-fat diet (10% energy as fat).…”
Section: Overview Of C 20-22 3 Pufa Regulation Of Cell Functionmentioning
confidence: 99%